Pre-clinical interaction of ayahuasca, a brew used in spiritual movements, with morphine and propofol - Júlia Movilla Pires; Fúlvio Rieli Mendes; Ana Paula Salum Pires; Maurício Yonamine; José Luiz Gomes do Amaral; Elisaldo Araújo Carlini (Universidade de São Paulo, 2018)
ABSTRACT Ayahuasca is a beverage with psychoactive properties used in religious and ceremonial rituals by some religious groups. The main active components of ayahuasca are dimethyltryptamine and the harmala alkaloids with β-carboline structure acting as monoamine oxidase A inhibitors. This combination produces a pronounced activation of serotonergic pathways and presents potential interaction with other psychotropics. The objective of this study was to investigate the possible interactions between ayahuasca and agents employed in general anesthesia. The pharmacological interactions between ayahuasca and morphine or propofol were evaluated in mice using doses of 12, 120 and 1200 mg/kg (0.1 to 10 times the average dose consumed by humans in religious rituals). Ayahuasca alone showed an antinociceptive effect in the writhing and formalin tests, and intensified the analgesic effect of morphine in the hot plate test. Concerning the pharmacological interactions between ayahuasca and propofol, the results were opposite; ayahuasca intensified the depressant effect of propofol in the rotarod test, but decreased the sleeping time induced by propofol. These set of results showed the occurrence of some interactions between ayahuasca and the drugs morphine and propofol, possibly by both pharmacokinetics and pharmacodynamics mechanisms.